Three essays on asset pricing - Li, W (2024)
This thesis encompasses three original research studies in asset pricing, accompanied by an introduction, a comprehensive literature review, and concluding remarks. The first two studies delve into the term structure of equity returns, while the third study centres on tax-loss harvesting with ETFs.